Carrier Concept in Hindu Religious Scriptures and Sculpture: A Conspectus - Panda, Taranisen; Mohanty, Rajballav B. (International Journal of Culture and Art Studies, 2021)
The relationship between man and bioresources (plants and animals) based on faith, belief, and tradition concerning gods and goddesses and other such powers are very intense, vast, and multifarious. The paper has a brief account of faith related to carrier or vahana in Hindu religious scriptures and sculpture. A total of 32 animals, ten different categories of birds, and only one plant (flower) are identified, playing the role of carriers of gods and goddesses of the Hindu pantheon. It is discussed that such faith, belief, and practice have a scientific basis and are helpful for the management and preservation of biodiversity.